(untitled) - Williams, Rosalind H. (Berkeley, 1982)
In Dream Worlds, Rosalind Williams examines the origins and moral implications of consumer society, providing a cultural history of its emergence in late nineteenth-century France.
Keywords: Consumers,Người tiêu dùng; History,Lịch sử; France,Nước Pháp